Calcifying Epithelial Odontogenic Tumour of the Mandible: An Unusually Aggressive Presentation of an Indolent Tumour - Dev, DP Arul (J Clin Diagn Res, 2016)
Calcifying Epithelial Odontogenic Tumour (CEOT) or Pindborg tumour is a rare odontogenic tumour of epithelial origin. They constitute less than 1% of odontogenic tumours. Intra-ossseous variant of CEOT are more common compared to extra-osseous variant. Although benign, these can exhibit deceptively aggressive presentation. Here we report a rare case of CEOT in a 36-year-old female patient who presented with aggressive intra-osseous lesion with cortical breach and exuberant soft tissue proliferation. The lesion was treated with resection and reconstructed with titanium reconstruction plate.